The influence of feminization in public relation field towards public relation work practice and job satisfaction - Veerappan, Geetha; Michael, Edwin; Abu Bakar, Afi Roshezry; Mariadass Lourdas, Mariann Edwina; Ibrahim, Ira Meilita; Ng, Meei Shy (2011)
Woman entering the public relations field has increased at a fast rate nowadays causing the phenomenon of feminization to occur in the industry.Studies in the field have shown that female public relations practitioners are facing challenges in the workplace especially sexual discriminations.Therefore it is important to identify the working trends in the current industry, roles, and the position of women in public relations field.The objective of the research is to find out how women’s roles are being distinguished from men and to examine whether feminization in the field does influence the job performance of women in the field.Thus, this research also aims to explore the perception of female public relations towards gender issues happening in the work place.This research is carried out through an online survey questionnaire to gain feedback from 450 targeted respondents.In the research, researches identified the reasons and effects with regards to this issue.According to the concept of velvet ghetto there is an argument on the status discrepancy between men and women in the industry.From the perspectives of theoretical contributions, this study offers an insight which indicates the relationship between gender discrimination climate happening in the organization and the effect to the job satisfaction which is interrelated to the work practice and advancement in an organization.Researchers also identify the elements that cause the phenomenon to occur, which have an impact on both employer and employee relationship. The findings demonstrate a good fit to the data, and thus, this study has identified the relative relationship between gender discrimination and job satisfaction.